Kindergarten Teachers’ Perspectives on Culturally Responsive Education - Alaca, Betül; Pyle, Angela (Canadian Journal of Education/Revue canadienne de l'éducation, 2018)
Six kindergarten teachers in the Greater Toronto Area were interviewed on their understandings of and approaches to culturally responsive education (CRE) in their classrooms. Teachers generally reported believing that CRE is important in kindergarten, and the practices they implemented fell into two categories: structured components of their classrooms and spontaneous accommodations or instruction. Teachers reported finding it challenging to access the resources they need to effectively practise CRE and to maintain ongoing communication with other school personnel and families. The implications of the findings are discussed to facilitate the development of age-appropriate CRE practices for kindergarten.